The ice age - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Surviving history., 2021)
Explores what life was like during the Ice Age, and provides questions for readers to test their survival skills. Includes color photographs, sidebars, activities, a glossary, and additional resources.